Furin Expression in Patients With Psoriasis—A Patient Cohort Endangered to SARS-COV2? - Graier, Thomas; Golob-Schwarzl, Nicole; Weger, Wolfgang; Benezeder, Theresa; Painsi, Clemens; Salmhofer, Wolfgang; Wolf, Peter (Frontiers in Medicine, 2021)
Background: SARS-Cov2 has raised concerns among dermatologists regarding psoriasis and its respective treatments. Comorbidities, which induce the expression of the proprotease furin have been associated with severe course of COVID-19. Furin and angiotensin converting enzyme 2 (ACE2) play a major role in viral host cell entry of SARS-Cov2. Objective: To evaluate mRNA expression of Furin and ACE2 from blood cells in psoriasis patients, and whether systemic or topical treatment reduces expression levels. Methods: This observational translational study analyzed blood samples from patients from a clinical trial and samples retrieved from the biobank of the Psoriasis Registry Austria (PsoRA). Furin and ACE2 expression levels were analyzed prior to as well as 3 and 12–24 months after start of biologic treatment with either ustekinumab or secukinumab. Additionally, the study analyzed expression levels prior to, 6 days after start of dithranol treatment and 4–6 weeks after end of dithranol treatment. Results: Furin mRNA expression was significantly increased at baseline in the biologic (4.9 ± 2.6 fold, p < 0.0001) and in the dithranol group (2.7 ± 1.4 fold, p < 0.001) compared to controls. There was a trend for arthritis patients to express more furin than patients with psoriatic skin involvement only (5.26 ± 2.30 vs. 3.48 ± 2.27, p = 0.078). Analyzing furin mRNA expression after treatment initiation with secukinumab or ustekinumab revealed a normalization of levels after 3 and 12 to 24 months. Similar findings were obtained for patients treated with dithranol, with significantly decreased expression levels 6 days after start of dithranol treatment and also at follow-up, (4–6 weeks after dithranol treatment had been terminated). ACE2 expression levels did not differ from controls at any timepoint, regardless of biologic or topical treatment. Conclusion: Significantly overexpressed levels of furin were observed in untreated patients, and, thus, these patients may be at risk for infection and a severe course of COVID-19. However, the data indicate that successful therapeutic intervention in psoriasis, by systemic biologic or topical treatment, can efficiently reduce furin levels in blood cells, possibly limiting the risk of psoriasis patients for a severe COVID-19 course. Clinical Trial Registration:ClinicalTrials.gov, identifier NCT02752672.